Sales subject to a condition in Islamic law: a juristic analysis - Rahman, Md. Habibur; Amanullah, Muhammad (Academy of Islamic Studies, UM, 2016)
In the contemporary period, there is hardly any transaction that is detached from its respective terms and conditions. This study aims to explore and analyze the issue of sale subject to a condition from the viewpoints of various schools of Islamic law. This study was accomplished through the scrutiny of the related primary sources of these schools. The researchers have found that the judgment of a sale with conditions is subject to the status of the related condition itself. Any condition that conforms to the requirements of the contract and customs is valid; otherwise it is invalid. Similarly, the study posits that the ruling of the contemporary transaction with terms and conditions is subject to the status of relevant conditions. If the condition is consistent with the contract and Shariah, it is valid and effective. Any condition that contradicts the requisites of the contract and Shariah are invalid and accordingly invalidate the transaction as well.